Patients with aortic stenosis have von Willebrand factor abnormalities and increased proliferation of endothelial colony forming cells. (22nd January 2020) - Selvam, Soundarya N.; Bowman, Mackenzie; Inglis, Madeline; Kloosterman, Robert; Grabell, Julie; Casey, Lara; Johri, Amer M.; James, Paula
Abstract: Background: Patients with aortic stenosis (AS) can experience bleeding complications including gastrointestinal bleeding from angiodysplastic lesions due to acquired von Willebrand syndrome. Studies have pointed to a role for von Willebrand factor (VWF) in angiogenesis. Objective: The objective of this study was to assess VWF defects in AS patients over time and the impact on angiogenesis using patient‐derived endothelial colony‐forming cells (ECFCs). Patients/Methods: Plasma sample collection and ECFC isolations were performed before valve replacement surgery, 3 to 5 days after, and 6 months after surgery. Plasma VWF antigen, activity, propeptide, collagen binding, multimers, factor VIII coagulant activity, and ADAMTS13 activity (a disintegrin‐like and metalloprotease with thrombospondin type 1 motifs 13) were determined. ECFCs were assessed for VWF and angiopoietin‐2 (Ang‐2) storage and secretion, cell proliferation, and tubule formation in Matrigel. Results and Conclusions: Aortic stenosis patients exhibited quantitative and qualitative abnormalities of VWF including significantly increased VWF antigen, activity, and propeptide levels following surgery ( P  < .01). Increased high molecular weight VWF multimers were observed at all time points and in particular 3 to 5 days after surgery (mean = 14% ± 6%) relative to before (mean = 10% ± 4%), suggesting increased proteolysis by ADAMTS13 pre‐operatively in a shear‐dependent manner. ECFCs from patients with aortic stenosis were more proliferative than controls ( P  < .05) and had increased retention of Ang‐2 ( P  < .05) suggesting epigenetic modification of the cells. Overall, there are hemostatic changes in AS patients that are present before valve replacement surgery and these persist long after surgery has occurred. These findings have implications for the current clinical management of AS patients.